Bureaucratic Reform and the Fight Against Corruption: Between Idealism and Reality (Indonesian Anti Corruption Studies, 2024)
Bureaucratic reform is widely promoted as a critical strategy for reducing corruption and enhancing public sector efficiency. This paper investigates the implementation and outcomes of bureaucratic reform initiatives in Indonesia’s anti-corruption efforts, focusing on policy design, institutional capacity, and frontline bureaucrats’ behaviors. Using a mixed-methods approach that includes policy document analysis, surveys of public servants, and case studies of reform programs, the study identifies key factors shaping the gap between reform ideals and practical realities. Findings reveal that while reforms have introduced modern management techniques and accountability measures, persistent challenges such as entrenched patronage, limited resources, and resistance to change undermine their effectiveness. The study argues that without addressing underlying political and cultural factors, bureaucratic reforms risk being symbolic rather than transformative. This research contributes to broader debates on governance reform by emphasizing the need for holistic approaches that integrate technical, political, and social dimensions to combat corruption in developing democracies like Indonesia.